(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze the causes of health insurance (HI) claim denials for medical examination and treatment at Tam Phuc Eakar General Clinic in 2024. Methods: A cross-sectional study employing both quantitative and qualitative approaches. Quantitative data were obtained from settlement reports between Tam Phuc Eakar General Clinic and the Dak Lak Social Insurance Agency. Qualitative data were collected through six in-depth interviews using a structured questionnaire administered to personnel directly involved in managing and processing HI reimbursement claims. Results and Recommendations: Three major groups of causes were identified: non-compliant procedure indications (92.7%); administrative and data-entry errors (6.2%); and inappropriate prescribing (1.1%). Root causes included insufficient dedicated HI staff, incomplete updating of regulatory documents, limitations in information technology, and the absence of a rigorous internal auditing process. Accordingly, the clinic should coordinate with Dak Lak Social Insurance to provide periodic training for all medical, administrative, and accounting staff on updated HI reimbursement regulations. Establishing an internal audit team to review claim files prior to submission, implementing checklists and periodic reports on recurrent errors, and upgrading the IT system to ensure data synchronization with the Social Insurance Portal—together with integrating automated alerts for ICD coding, technical norms, and drug lists—are also recommended.